Case Report: Electro-cortical network effects of an acute stroke revealed by high-density electroencephalography - Monai, Elena; Sevak, Brinda; Gjini, Klevest; Pini, Lorenzo; Tononi, Giulio; Struck, Aaron F.; Boly, Melanie (Frontiers in Neuroscience, 2025)
IntroductionFocal lesions such as a stroke can cause not only local effects but also distant effects in anatomically intact regions. The impact of stroke lesions on brain networks has been mapped using neuroimaging techniques such as functional magnetic resonance imaging (fMRI) and diffusion tensor imaging (DTI). In the present study, we established the feasibility of detecting network dysfunction at the electrocortical level using high-density electroencephalography (HD-EEG).Case reportWe studied brain function using HD-EEG in a patient with an acute left middle cerebral artery stroke. Slowing in the delta range was present beyond the ischemic focus, extending to the perilesional regions as well as distant regions. There was also delta connectivity in the stroke hemisphere with slowing affecting mainly distant regions that were interconnected with the site of the ischemic region (i.e., network-level diaschisis), although this was not statistically significant.ConclusionThis case study illustrates the feasibility of using HD-EEG to map local and distant electrical activity consequences of an acute stroke on cortical functions. Such a technique could be clinically useful to improve personalized stroke-network mapping in patients with acute cortical lesions.